Constraining the LMC age gap: Washington photometry of NGC 2155 and SL 896 (LW 480) - Piatti, Andres Eduardo (2002)
We carried out Washington system photometry of the intermediate-age Large Magellanic Cloud (LMC) star clusters NGC 2155 and SL 896 (LW 480). We derive ages and metallicities from the T_1 versus C-T_1 colour-magnitude diagrams (CMDs). For the first time an age has been obtained for SL 896, 2.3 +/- 0.5 Gyr. For NGC 2155 we derive 3.6 +/- 0.7 Gyr. The two clusters basically define the lower age limit of the LMC age gap. In particulr, NGC 2155 is confirmed as the oldest intermediate-age LMC cluster so far estudied. The derived metallicities are -0.9 +/- 0.2 and -0.6 +/- 0.2 for NGC 2155 and SL 896, respectively. We also studied the CMDs of the surrounding fields, which have a dominant turn-off comparable to that of the clusters themselves, and similar metallicity, showing that one is dealing with an intermediate-age disc where clusters and field stars have the same origin. We inserted the present clusters in the LMC and Small Magellanic Cloud (SMC) age-metallicity relations, using a set of homogeneous determinations with the same method as in our previous studies, now totalling 15 LMC clusters and four SMC clusters, together with same additional values from the literature. The LMC and SMC age-metallicity relations appear to be remarkably complementary, since the SMC was actively star-forming during the LMC quiescent age gap epoch.